The Influence of Hand Puppet Media on Early Childhood Story Listening Skills - Nurrohmatul Amaliah; Zalfa Afifah; Arum Fatayan (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to determine the effect of using hand puppet media on story-listening skills in children aged 5-7. The method used in this study is a quasi-experimental research design with a control group pretest-posttest design. This study took a sample of 32 experimental and 32 control class students. The instrument of this research is a test. The data analysis technique used the SPSS Statistic 25 program. Based on the study results, it can be seen from the comparison of the average pretest and post-test of the experimental and control classes. In other words, the use of learning media for children aged 5-7 years, both hand puppets and paper puppets, have the same effect on story-listening skills.